Drying of instant coffee in a spray dryer - Nur Tantiyani Ali Othman; Muhammad Elmi Fahmi Mohd Razali (Penerbit Universiti Kebangsaan Malaysia, 2019)
Instant coffee is a popular beverage around the world and has been recognized for shorter preparation time and longer shelf life compared to brewed coffee. The production of instant coffee powder through the drying process requires lots of attention to provide the best quality of coffee to the consumer. Most of the instant coffee powder has been produced either by freeze-drying or spray drying. However, the drying spray showed some advantages in case of shorter drying time, ability to handle in a large capacity, and continuous production of coffee powder compared. The objective of this study is to identify the affecting factors in achieving a high quality of coffee production in the drying process. The initial concentration of coffee extract is between 30-42 wt.% were fed by the atomizer. Also, the spray drying chamber with the inlet air temperature of 423.15 K to 573.15 K. The pressure was set at 52 bar to obtain the best drying quality of the coffee production. The simulation results show with the air temperature of 423.15 K, the pressure of 52 bar and the initial extract concentration of 42% are the best conditions of drying coffee using the spray drying method. Also, the velocity distribution flattened as the flow proceeds downstream. As well, the vapour concentration distribution flattened further down the chamber so that the drying air leaving the drying chamber has almost a uniform moisture distribution.